Become Captain of Your Financial Ship, Unit 3: Standing Watch - Josephine Turner (EDIS)
FCS7223, a 32-page curriculum by Josephine Turner, is Unit 3 in a series on personal financial management. It includes a slide presentation, money management newsletters, credit report request forms, fact sheets, and worksheets on debt management and debt dangers, using credit, and how to request a credit report. Published by the UF Department of Family, Youth and Community Sciences, January 2007.